A critical review for travel satisfaction and subjective well-being - Dong, Hao; Hashim, Haslinda; Kamarulzaman, Nitty Hirawaty (Elsevier, 2024)
Introduction: Travelers increasingly consider their emotional needs when making travel mode choices. While travel satisfaction (TS) is insufficient for a comprehensive evaluation of travel modes, subjective well-being (SWB) has gained attention. However, the relationship and differences between subjective well-being and TS have yet to receive adequate attention. Method: This study aims to clarify the correlations and differences between TS and subjective well-being from three aspects: definition, current research, and relationship mechanism, using a literature review method. Results: The study results show that (1) TS can be seen as a component of the definition of subjective well-being. (2) Further research is needed on both subjective well-being and TS in the Chinese context. (3) Subjective well-being provides a more accurate and comprehensive representation of passengers’ evaluations of travel modes than TS. From another perspective, TS is more suitable for measuring the influence of emotional factors on travel mode choice. Conclusions: The result provides a valuable reference for understanding subjective well-being and TS, distinguishing the differences between the two concepts and the research value of both. It helps marketers develop and implement effective marketing strategies to encourage passengers to choose eco-friendly travel modes.